Relationship between Myhers-Briggs personality types and stress levels among University of the Philippines College of Dentistry Studetns (A.Y. 2018-2019) - Salazar, Nica Jeorgia P.; Alfaro, Arlene Cecilia A. (Manila Department of Community Dentistry, University of the Philippines Manila, 2019)
Introduction: In UPCD, the students have a wide array of personalities that may predispose them to higher or lower levels of tolerance to stress. In order to perform well, a student must possess a certain essential physical, cognitive and emotional abilities. This includes having to work under pressure and displaying flexibility and adaptability to changes in the environment. The aim of the study is to determine the relationship between the personality types and the stress levels of University of the Philippines College of Dentistry (UPCD) students (A.Y 2018-2019).
Methodology: A cross-sectional correlational study was conducted among UPCD students through an online survey. The online survey was made open to the student body for three weeks, with a turnout of 122 respondents (31% of the student body). The survey consisted of some demographic information about the respondents, Myers?Briggs Type Indicator (MBTI) and Depression, Anxiety, Stress scale (DASS-21). ANOVA was used to analyze the results of these tests to know if there exists a relationship between the personality types of the students and their stress levels.
Conclusion: There was no correlation between personality types and stress scores, it can be inferred that any personality type can be affected by stress. It is important to plan effective intervention programs to help students better manage stress.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Myers-Briggs Type Indicator; DASS-21.